Sewing Plates can be Used for Optimization of Child-Fine Motorized (the CP Large) of Brain Training - Wardhani, Rr Dina Kusuma; Rusmono, Rusmono; Wuryani, Wuryani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to help students with cerebral palsy in TKLB SLB D YPAC in southern Jakarta improve their fine motor skills. School learning model design tool effectiveness and reliability, supported by test results, ADDIE (Analysis - design - implementation - assessment) method is used to study the development model used in this study. Researchers present the data results in the form of analysis and facts based on the theories used in this research. The discussion of the presentation is based on research and evidence in the field and has been adjusted according to the theory used in this research to improve fine motor skills. Use media sewing board, South Jakarta TKLB SLB D YPAC cerebral palsy (CP) The student can understand him their illness. After extensive research and development, resulting sewing board has been shown to improve cerebral palsy (CP) fine children's fine motor skills.